Pengenalan Microsoft Word Pada Usia Dini Kepada Yayasan Roemah Tawon - Muhammad Faisal; Ahya Mahfuzi; Nisan Yedidiya Sorayana Mendrofa; Azis Saputro; Muzakki Hafizh; Muhammad Ikhwal; Annis Syifa; Rizky Prasetyo; Muhammad Yusuf; Abdul Majid; Perani Rosyani (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Manage data and store information (data storage) practically and efficiently. In today's digital era, computer-based information and communication technology has influenced various aspects of life, including education, it is undeniable. This community service activity aims to provide assistance to participants of the ROEMAH TAWON Foundation in applying Microsoft Word. With this activity, it is hoped that it will make it easier for students to do word processing and make useful presentation media to facilitate the learning process. The method used in an effort to achieve the planned target or goal is the explanation of the material, practice (performance) and question and answer. The trainees are divided into groups. Each group was accompanied by one of the university students. To find out the success of the program activities that have been carried out, an evaluation is carried out. Evaluation is done by giving practical exams to determine the level of understanding of students regarding the material and training that has been provided. The conclusion of this activity is that community service has succeeded in increasing students' knowledge in the application of Microsoft Word. The students of the ROEMAH TAWON Foundation felt helped by the training that was carried out so that they could use computers or laptops in doing school assignments well, such as making papers to facilitate activities. Students gave a very positive response to the activities carried out and considered this activity very useful